Developing a head-mounted tactile prototype to support situational awareness. Issue 109 (January 2018) - Wolf, Flynn; Kuber, Ravi
Highlights: Development of a head-mounted tactile prototype to support situational awareness (SA). Presenting information relating to users' surroundings can support decision-making. Examined the user's ability to discern multi-parameter tactons at the head. Investigated how the use of the tactile coding scheme impacted levels of SA. Guidelines from the research can support interface designers. Abstract: In this paper, we describe the design and evaluation of a head-mounted tactile prototype and multi-parameter coding scheme to support situational awareness among users. The head has been selected as the location for the interaction because it has been relatively under-researched compared to the torso or hands, and offers potential for hands-free attention direction and integration with new head and eyewear technology. Two studies have been conducted. The first examined the user's ability to discern three-parameter tactile signals presented at sites on the head. Findings highlighted that while multi-parameter cues could be interpreted with low error, challenges were faced when interpreting specific combinations of waveform and interval type, and when performing identification of interval pattern and stimulation location while visually-distracted. A second study investigated how use of the three-parameter tactile coding scheme impacted participants' situational awareness under several exertion conditions. Significant interaction was found between the exertion conditions and subjective cognitive workload. The relationship between situational awareness phases of participant SAGAT assessment scores were consistent between conditions, with perception and prediction phases outpacing comprehension. This suggests, pending further study of the suitability of situational awareness evaluation methods for tactile perception, that quickly trained participants may struggle to understand multi-parameter coding intended to convey changing events. Interpretations of coding schemes were found to vary, highlighting the importance of carefully selecting and mapping signals for presentation. Insights from our study can support interface designers aiming to heighten levels of spatial and situational awareness among their users through use of the tactile channel.